Pembentukan Karakter Anti Korupsi Kepada Siswa SMA YPPK Teruna Bakti - Dwight Nusawakan; Sri Nur Damayana; Nur Sri Maryam Dm; Nurul Chaerani Nur; Abdul Malik Mufty; Heryanto Heryanto; Magdhalena Tasik Todingrara; Vivilia Agnata Mudi; Muh. Anugrah Kurniawan Amir; Ayub Jose Luhut Parulian Simanjuntak (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Eradicating corruption is a top priority to improve people's welfare and strengthen the Unitary State of the Republic of Indonesia (NKRI) and in order to achieve national goals. Therefore, the policy of optimizing corruption eradication must be followed up with a comprehensive, integral, and holistic strategy in order to truly achieve the expected results. Prevention and preventive actions will be more useful in overcoming corruption problems than taking high legal sanctions. This shows that corruption prevention must be optimized properly in eradicating corruption in Indonesia. Therefore, providing knowledge to High School Students in Jayapura City, Papua Province about how to prevent Corruption is very important so that they can avoid themselves from Corruption